Investigation on Optically Ultraviolet Response of Low-dimensional ZnO Structures Prepared by Chemical Processes - P Pintupimol; W Sinornate; W Pecharapa (My University, 2023)
Abstract Chemical processes were used to synthesize ZnO low-dimensional structure including ZnO thin film ZnO nanorod and ZnO nanoparticle. ZnO thin film was prepared by sol-gel spin coating method while ZnO nanorod was prepared by hydrothermal process and ZnO nanoparticle was synthesized via co-precipitation route. The structural, morphological, optical and photoresponse properties were investigated by XRD, FESEM, UV-Visible spectrophotometer, I-V and I-t measurement. Comparison study on photoresponse properties of all structures was conducted under UV light with UV LED wavelength 375 nm. The UV photodetector based on ZnO nanoparticle sample showed superior photoresponse time to another ZnO low-dimensional structures. The results informed crucial factors including active surface area per volume, interaction in low-dimensional structures and specific properties in each structure playing key role on optical ultraviolet response.
Keywords: Nanorod; Ultraviolet; Spin Coating; ZnO doping and properties